Maximizing Pleurotus ostreatus yield with sustainable agricultural waste substrates in Arakan, Cotabato, Philippines - MAYBELYN LUPAS PEDROSO; ANNIE LEE CAYABAS ALAGOS; FRANCISCO JR. OLERMO ESGRINA; JOEFREY FEROLIN HABIBUN; JOSIE NACIONALES MAUN; RICHIE MAE MONDIDO RODRIGUEZ (Smujo International, 2025)
Abstract. Pedroso ML, Alagos ALC, Esgrina FJO, Habibun JF, Maun JN, Rodriguez RMM. 2025. Maximizing Pleurotus ostreatus yield with sustainable agricultural waste substrates in Arakan, Cotabato, Philippines. Nusantara Bioscience 17: 57-67. Mushroom production supports a circular economy by transforming agricultural waste into valuable food resources while enhancing local agricultural economies. This study evaluates the potential of locally available agricultural waste substrates-chopped rice straw, aged rice hull, rough sawdust, and fine sawdust-for optimizing the production of oyster mushrooms (Pleurotus ostreatus (Jacq.) P.Kumm. in Arakan, Cotabato, Philippines. The effects of these substrates on key growth parameters, including mycelial growth, fruiting time, yield, and economic returns, were assessed. A Completely Randomized Design with five replicates per treatment was employed, using a substrate mixture of 89% agricultural waste, 10% molasses, and 1% lime. Statistical analysis revealed that fine sawdust facilitated faster mycelial growth and reduced fruiting time, whereas rough sawdust produced higher yields and larger mushrooms. Economic analysis indicated that rough sawdust yielded the highest return on investment at 190.21%, making it the most cost-effective substrate. These findings demonstrate the potential of agricultural waste as a sustainable substrate for oyster mushroom cultivation, promoting environmental sustainability and profitability for small-scale farmers. The study emphasizes the critical role of substrate selection in optimizing mushroom yield and provides practical insights for commercial mushroom production.